Modeling, design, and experimental test of a zero-sequence current electromagnetic suppressor - Leal Freitas, Stefani Carolline; Origa de Oliveira, Luis Carlos [UNESP]; Oliveira, Priscila da Silva; Exposto, Bruno; Oliveira Pinto, Jose Gabriel; Afonso, Joao Luiz (Wiley-Blackwell, 2020)
This paper presents the experimental investigation of an electromagnetic suppressor to minimize the circulation of zero-sequence currents in three-phase four-wire distribution systems. The proposed zero-sequence current electromagnetic suppressor (ZSS) integrates two distinct electromagnetic devices, namely a zero-sequence filter (ZSF) and a zero-sequence blocker (ZSB), connected in parallel and in series between the source and the load, respectively. In this paper are presented the theoretical modeling and analysis of each device, the mathematical concepts of harmonic compensation, and the procedures for the design and determination of the constructive details. The experimental results of the combined operation of the devices that integrate the ZSS demonstrate the feasibility of the proposed arrangement, by minimizing the flow of the zero-sequence harmonic currents in the source side, enabling a significant reduction of the current in the neutral conductor, and also by improving the system power factor.
Keywords: electromagnetic suppressor; harmonics; passive filter power factor; zero-sequence currents